Insights into mode of action mediated responses following pharmaceutical uptake and accumulation in plants - Garduño-Jiménez, Andrea-Lorena; Carter, Laura J. (Frontiers in Agronomy, 2024)
The reuse of wastewater to meet irrigation requirements and slurries, sludges and manures as fertilisers to meet crop nutrient demands inadvertently introduces human and veterinary-use pharmaceuticals into the agro-ecosystem. This review synthesises recent research, which has observed sub-lethal effects, following pharmaceutical uptake by plants. Potential links between pharmaceutical mode of action and observed sub-lethal effects in the plant were then examined. Common receptors and biological pathways across species suggests a clear need to integrate plant cellular biology into our understanding of the impacts of pharmaceuticals on important plant functions and processes. To help prioritise future research efforts an analysis of shared mammalian and plant biochemical pathways was undertaken to identify classes of pharmaceuticals which may present a greater risk to key plant functions. These included sulfonylurea antihyperglycemics, steroids, opiods, antipsychotic phenothiazines and pharmaceuticals targeting several neurotransmitters shared between mammals and plants (including beta-blockers, antihistamines and benzodiazepines). Whilst a number of pharmaceutical induced sub-lethal effects have been observed, this review highlights the clear need to study a wider range of pharmaceuticals on a broader range of plant species, including cover crops and wild plants, under realistic exposure scenarios, to fully understand the wider implications of pharmaceutical exposure in agro-ecosystems. State-of-the art omics-techniques offer great potential to understand the mode of action of pharmaceuticals in plants and elucidate links between the pharmaceutical intended mode of action and observed plant effects. In addition, studies under co-stress from pharmaceutical exposure and other stressors such as increased temperatures, drought or pests are lacking and present an urgent research need in the face of feeding a growing population under the threats of climate change.